2011
DOI: 10.1038/bmt.2011.108
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of metastatic retinoblastoma with high-dose chemotherapy and autologous stem cell rescue in South America

Abstract: High-dose chemotherapy (HDC) followed by autologous stem cell rescue (ASCR) is the only curative treatment for metastatic retinoblastoma, but its feasibility in developing countries is unknown. We report 11 consecutive children (six unilateral) treated in three South-American middleincome countries with HDC-ASCR. One patient had metastatic retinoblastoma at diagnosis and the remaining ones had a metastatic relapse. Metastatic sites included BM ¼ 6, bone ¼ 4, orbit ¼ 5 and central nervous system (CNS) ¼ 4. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Therapeutic options for most patients who progress or relapse are limited; however, some patients with relapsed or metastatic disease can be effectively treated with autologous stem cell transplantation (13,14). At baseline, PET/CT can identify patients at high risk for relapse, and similarly during response assessment PET/CT can identify disease progression before it manifests clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options for most patients who progress or relapse are limited; however, some patients with relapsed or metastatic disease can be effectively treated with autologous stem cell transplantation (13,14). At baseline, PET/CT can identify patients at high risk for relapse, and similarly during response assessment PET/CT can identify disease progression before it manifests clinically.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, 11 patients with metastatic disease were treated with high-dose chemotherapy and autologous hematopoietic stem cell rescue therapy, with disease-free survival reported in 7 patients after 39 months. 52 Four patients with CNS involvement died due to recurrence occurring an average of 7 months later.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, South American investigators reported 11 children with stage 4a or 4b disease and noted that 7 were disease-free with a median follow-up of 39 months, indicating that this strategy may also be effective in middle-income countries [ 22 ].…”
Section: Confi Rmatory Case Seriesmentioning
confidence: 98%